PENGARUH DER, EPS, RESIKO SISTEMATIS DAN KEBIJAKAN DEVIDEN TERHADAP HARGA SAHAM PERUSAHAAN YANG TERDAFTAR DI BEI (Studi pada Perusahaan yang masuk dalam Indeks Saham LQ45 Periode 2010-2012) - Novianingtyas, Riska; dro, Harlen (Jurnal Ilmiah Mahasiswa FEB, 2013)
The purpose of this research is to know the influence of variable Debt Equity Ratio (DER), Earning Per Share (EPS), a systematic Risk (Î²), and the Dividend Poyout Ratio (DPR) against stock prices on companies listed on the Indonesia Stock Exchange (BEI). In this study the population is the successive LQ45 company has been listed on the BEI in the period of 2010-2012 as many as 45 companies. The techniques used in this research is the saturated sample or census whereby all members of the population used as samples. So the sample in this research is all Jsx LQ45 as much as 23 companies. Test the hypothesis in this study using multiple linear regression analysis. The test statistic t is used to find out the magnitude of the effect of each independent variable on an individual basis (partial) of the dependent variable. Statistical tests are used to determine the influence of F are jointly the dependent variable to the independent variable. The results of this research show that simultaneously, using Test-F, variable DER, EPS, Systematic Risk (Î²), and the Dividend Payout Ratio (DPR) have an effect on the price of shares in companies listed on the BEI. While based on Test-t only variable EPS influence partially against stock prices on companies listed on the BEI. The dominant influence of EPS variables to stock price. This research resulted in coefficients of determination adjusted (Adjusted R2) of 0,424. Those results show variations in share prices that are described by variables DER, Systematic Risk, EPS, Dividend Policy and the regression equations in only amounted to 42.4%, whereas the rest of 57.6% explained by variables other than the equation model. Keywords: DER, EPS, Systematic Risk, and policy Dividends, stock price, Multiple Linear Regression.